FROM THE IMAGE OF GOD TO THE KINGDOM OF GOD: The Church as a Creative Space - Elavathingal, Sebastian (Asian Horizons, 2012)
The Second Vatican Council made a significant effort to contextualize the Church in the modern world. The Pastoral Constitution Gaudium et Spes undertakes this task by “scrutinizing the signs of the times and of interpreting them in the light of the Gospel.”1 The Church has to be prepared to face the realities of the world and to respond to them creatively by being more sensitive to the changing world and less prone to institutionalization. In this new self-understanding the Church rediscovers its “relational” nature which has for centuries remained overshadowed by its institutional structures. In order to be relevant and meaningful in today’s world and to realize its destiny the Church has to be a dynamic, creative community